Synthesis And Characterization Of Fexoy Doped Tio2 Immobilized On Activated Carbon For Degradation Of Single And Binary Mixture Of Methylene Blue And Methyl Orange Dyes Under Visible Light - Razali, Nurul Fitrahanis (2018)
The purpose of this study is to produce the photocatalyst that has good photocatalytic activity under visible light. In this study the modification of TiO2 was conducted by immobilization of TiO2 on 10% wt activated carbon (TiO2-10% AC) and FexOy doping of different Fe weight percentages (0.1, 0.5, and 1% wt) on the TiO2-10%AC using a sol-gel method. The effects of FexOy doping and immobilization onto AC towards the removal efficiency of single dye methylene blue (MB) and methyl orange (MO), and binary dye mixtures of MB and MO were compared to pure TiO2. The X-ray diffraction (XRD) analysis showed that the crystallite size of TiO2 decreased from 56.5 to 24.4 nm after immobilization onto AC, while the surface area increased from 114 to 204 m2 g-1 as the % wt of the dopant increased. In fact, the band gap of the anatase phase of TiO2 was also reduced from 3.15 to 2.8 eV as the % wt of FexOy dopant were increased to 1%. The optimum parameters for the removal of single MB and MO dyes were determined to be 0.10 g of the catalyst dosage, 75 mg/L of MB, 50 mg/L of MO, at ambient pH with the contact time of 2 h. Meanwhile, the parameters for the binary dyes mixture were found to be optimum at a high concentration (mg/L) ratio of MB to MO (40:40) and at ambient pH with the contact time of 2 h. The 1% FexOy/TiO2-10% AC photocatalyst showed maximum removal of 93% for the MB dye with initial concentration of 75 mg/L, while the 0.1% FexOy/TiO2-10% AC showed up to 96% removal for MO with the initial concentration of 50 mg/L after 2 h of irradiation under normal laboratory light. The 0.5% FexOy/TiO2-10% AC photocatalyst showed the highest removal of binary dye mixture at the initial concentration ratio of 40:40 (mg/L) after 2 h of irradiation where 88 and 99% of MB and MO were removed, respectively. This study revealed that the immobilization of TiO2 onto AC improved the photocatalytic activity of the material. To increase the reusability of the photocatalyst, different desorbing agents such as H2O, NaNO3, H2SO4, and NaOH, were used and it was found that NaOH is the best eluent for MB but for MO none of the desorbing agent shows good desorption activity. The results showed that the treated photocatalysts can be repeatedly used although the percentage of removal decreased to 40% at the 10th and 3rd cycles for MB and MO, respectively.